Seed desiccation and salinity tolerance of palm species Carpentaria acuminata, Dypsis decaryi, Phoenix canariensis, and Ptychosperma elegans - Batista, Gisele Sales [UNESP]; Mazzini-Guedes, Renata Bachin; Pivetta, Kathia Fernandes Lopes [UNESP]; Pritchard, Hugh W.; Marks, Tim (My University, 2016)
Desiccation-sensitive seeds lose water quickly, what is an important feature to determine their ability to tolerate periods of seasonal drought. Furthermore, excess of soluble salts on seed germination causes a reduction in the substrate water potential. The objective of this study was to assess the desiccation and salinity tolerance of seeds of four ornamental palm species. Different moisture contents were studied for seeds of Carpentaria acuminata, Dypsis decaryi, Phoenix canariensis, and Ptychosperma elegans, while five concentrations of NaCl were tested separately for C. acuminata and P. elegans. Seeds of C. acuminata and P. canariensis tolerated drying at 5% and 8% seed moisture, respectively. On the other hand, seeds of D. decaryi and P. elegans were sensitive to dehydration even at high moisture contents, 20% and 27% of seed moisture, respectively. Increase on salt concentration did not affect germination or germination rate of C. acuminata and P. elegans seeds.
Keywords: Arecaceae; Electrical conductivity; Moisture content; Ornamental palms; Recalcitrant seed; Salt stress